1983
DOI: 10.1155/lc.1.211
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐Photon Infrared Laser Photophysics and Photochemistry. I

Abstract: This paper begins our review paper on the multiple-photon excitation of molecules by intense infrared laser light. The whole review will be given in installments. In this first part we bring forward certain general concepts on spectroscopy, molecular physics and chemical kinetics essential for understanding the later material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 37 publications
2
55
0
1
Order By: Relevance
“…When the laser frequency matches that of a normal vibrational mode of the gas-phase ion, energy is absorbed and subsequently distributed throughout the ion by intramolecular vibrational redistribution (IVR). The rapidity of the IVR process allows the energy of each photon to be "relaxed" prior to the absorption of the next, and thus allows promotion of the ion's internal energy to the dissociation threshold by multiple photon absorption [25]. Prior studies have shown that the infrared spectra obtained using the IRMPD method presented here are comparable to those obtained using linear absorption techniques [27,36,38].…”
Section: Infrared Multiple Photon Dissociation (Irmpd)mentioning
confidence: 63%
See 2 more Smart Citations
“…When the laser frequency matches that of a normal vibrational mode of the gas-phase ion, energy is absorbed and subsequently distributed throughout the ion by intramolecular vibrational redistribution (IVR). The rapidity of the IVR process allows the energy of each photon to be "relaxed" prior to the absorption of the next, and thus allows promotion of the ion's internal energy to the dissociation threshold by multiple photon absorption [25]. Prior studies have shown that the infrared spectra obtained using the IRMPD method presented here are comparable to those obtained using linear absorption techniques [27,36,38].…”
Section: Infrared Multiple Photon Dissociation (Irmpd)mentioning
confidence: 63%
“…In general, infrared spectra of the uranyl complex ions were collected by monitoring the efficiency of IRMPD as a function of photon energy [25]. In this experiment, isolated complexes were irradiated using two FELIX macropulses (40 mJ per macropulse, 5 s pulse duration, FWHM bandwidth around 0.5% of central ).…”
Section: Infrared Multiple Photon Dissociation (Irmpd)mentioning
confidence: 99%
See 1 more Smart Citation
“…The anharmonic force field calculations have been carried out. 6 The need for anharmonic correction to existing reaction rate theories has been emphasized by several authors, [7][8][9] and Troe 10 proposed a simple empirical method for generating anharmonic vibrational densities of states using experimental thermodynamic data.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have concentrated on the requirement for the anharmonic correction to previous reaction rate theories. [21][22][23] For this reason, using experimental thermodynamic data, J. Troe 24 presented a simple empirical method for generating anharmonic vibrational densitiy of states. In 2007, a method which can carry out the first principle calculations about the rate constants of molecular reactions within the framework of the transition state theory has been proposed by Yao and Lin (YL).…”
Section: Introductionmentioning
confidence: 99%